Cultural rhythms and pulses on MIS 5-3 migration episodes of Homo sapiens dispersal in Northeast Africa - Jürgen Richter; Karin Kindermann; Ralf Vogelsang; Felix Henselowsky (Quaternary Science Advances)
On the one hand, genetic observations suggest one essential migration of anatomically modern humans (AMH) from Africa to Eurasia had taken place around 70-50 ka BP and led to the dispersal of AMH all over the world (Out-of-Africa-II model). On the other hand, given the initial phase of the migration would have been located in East and Northeast Africa, archaeological patterning of cultural traits can, so far, neither support nor contradict such a model within the supposed area of migration, and at the time concerned hereby. This paper addresses the obvious invisibility of the migration in the archaeological record and the reasons for it. We propose the summer/winter rainfall frontier to have caused phases of isolation between East and Northeast Africa, impeding cultural exchange between these areas, either resulting from acculturation or migration. We exclude large scale events of dispersal, only small-scale movements of populations to be admitted. This might explain the lack of archaeological visibility of the migration event.